2014
DOI: 10.1002/pmic.201300529
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling and characterization of differential allergens in the nematodes Anisakis simplex sensu stricto and A. pegreffii

Abstract: The parasite species complex Anisakis simplex sensu lato (Anisakis simplex sensu stricto; (A. simplex s.s.), A. pegreffii, A. simplex C) is the main cause of severe anisakiasis (allergy) worldwide and is now an important health matter. In this study, the relationship of this Anisakis species complex and their allergenic capacities is assessed by studying the differences between the two most frequent species (A. simplex s.s., A. pegreffii) and their hybrid haplotype by studying active L3 larvae parasiting Merlu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 52 publications
3
46
0
Order By: Relevance
“…as a single pathogen even if A. pegreffii and presumably A. simplex s.s. have been identified in anchovies181920. Some studies have suggested differences between A. pegreffii and A. simplex s.s. in terms of immunopathogenicity capacity against humans515455. Humans may also have different susceptibilities to these zoonotic nematodes4.…”
Section: Discussionmentioning
confidence: 99%
“…as a single pathogen even if A. pegreffii and presumably A. simplex s.s. have been identified in anchovies181920. Some studies have suggested differences between A. pegreffii and A. simplex s.s. in terms of immunopathogenicity capacity against humans515455. Humans may also have different susceptibilities to these zoonotic nematodes4.…”
Section: Discussionmentioning
confidence: 99%
“…A range of allergens have been isolated from A. simplex and these can cause disease in sensitized patients even without exposure to the live worm (Caballero et al, 2011;Arcos et al, 2014;Faeste et al, 2014). Thus, ingestion of processed fish products with heat and frost stable worm allergens have been reported to elicit allergic reactions in consumers (Audicana et al, 1997) but it is generally believed that an active infection with a live penetrating Anisakis larvae is needed to sensitize and establish the allergic condition in patients (Alonso- Gómez et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Shad products are consumed fresh locally in the Iberian Peninsula and also in France (Elie et al 2000) and are likely to be reasonably safe, due to the Portuguese and Galician cultural traditions of eating heavily cooked food. Nevertheless, a potential health human risk exists since allergic reactions could occur due to thermostable allergens even if no live larvae reach the consumer (Sharp and Lopata 2014;Baird et al 2014, Arcos et al 2014. The recognition of several thermostable Anisakis antigens provoking allergic reactions, which can be highly aggressive and generate severe clinical manifestations, suggests that surveillance and epidemiological awareness should be encouraged.…”
Section: Risk Assessmentmentioning
confidence: 96%